Assessment of Turbulence Intensity in Different Spots of Lightning Flash Propagation. Issue 21 (1st November 2021) - Souza, Jessica C. S.; Bruning, Eric C.
Abstract: The updraft speed is correlated to the total lightning flashes a storm produces. Shear along updraft gradients is one of the mechanisms responsible for the production of turbulence kinetic energy (TKE). Thus, the radar‐estimated eddy dissipation rate (EDR) overlapped with Lightning Mapping Array (LMA) data is used to evaluate the storm's kinematic and electrical relationship. The majority of the sampled flashes shows higher turbulence intensities close to lightning initiation regions. As the distance from initiation increases along the lightning propagation path, there is a gradient to less turbulent regions. We identified small‐sized and medium‐sized flashes initiated at lower altitudes in regions of smaller EDR values consistent with the unmixed flow within inner part of updrafts. Furthermore, there were a concentration of small flashes initiated in the upper portion of the cloud in high EDR values due to their associated small‐scale variability. Plain Language Summary: The strength of the rising current within a thundercloud correlates with the intensity of turbulence production and the amount of lightning flash incidence. In this study, we evaluate the turbulence intensity in different parts along lightning flashes propagation. The results show that turbulence intensity is higher in locations closer to the lightning initiation and decreases as the distance from lightning initiation increases. However, there is also presence of lower intensity turbulence close to lightning initiation. Therefore, the results suggest a range of turbulence intensity favorable for lightning propagation and a minimum threshold for lightning initiation. Key Points: Observations of turbulence intensity along flash propagation support inertial range eddies' role in organizing charge in thunderclouds A gradient of small flashes in highly turbulent regions to larger flashes in less turbulent regions is observed The upper limit in turbulence intensity permitted for flash propagation in a region varied with the distance from flash initiation